(untitled) (GEOMATE Journal, 2025)
Liquefied stabilized soil is an earthwork material in which muddy water (or clear water) and solidification material are kneaded into construction soil or construction sludge in an appropriate composition and then poured into the casting place while maintaining fluidity. It is widely used in urban areas to fill narrow spaces, such as structural backfilling, where compaction is difficult. This study investigated the relationship between curing temperature and unconfined compressive strength of liquefied stabilized soil based on the maturity concept. Laboratory tests were conducted at temperatures of 20°C, 40°C, and 60°C with varying wet densities and different types of solidification materials (Normal Portland Cement, High Early Strength Portland Cement, and Portland Blast Furnace Slag Cement). The results demonstrated that higher curing temperatures significantly reduced the required curing time, with specimens at 60°C achieving target strengths (target unconfined compressive strength at 28 days under 20°C curing: 78.5-258 N/mm2) in approximately one-fourth the time compared to 20°C curing. The maturity equation, originally developed for cement-improved soil, was found to be applicable for predicting strength development in liquefied stabilized soil, particularly in the temperature range of 40-60°C, regardless of the type of solidification material used.